# 1. If f(x)=3x-4 and g(x)=x+2: find f-g 2. If f(x)=3x-4 and g(x) = x+2: find f-g Will someone help me solve these 2 problems and get the correct answers, my answers were incorrect. my answers...

1. If f(x)=3x-4 and g(x)=x+2: find f-g

2. If f(x)=3x-4 and g(x) = x+2: find f-g

Will someone help me solve these 2 problems and get the correct answers, my answers were incorrect.

my answers were:

1. x+2

2. 2x+2

### 6 Answers | Add Yours

f(x)=3x-4 g(x)=x+2

f(x)-g(x)=3x-4-x-2

Gathering the terms in x together and the free ones together, the result will be:

f(x)-g(x)= (3x-x)+(-4-2)=2x-6

*f(x)=3x-4 *g(x)=x+2

*f(x)-g(x)=3x4-x-2

*you have put x and the free ones together, my result is>>>

f(x)-g(x)= (3x-x)+(-4-2)=2x-6 **that is** my answer but 3x-x if you want not put () ok...bye..

if f(x)=2xsquare-x-3 and g(x)=x+1 find f=g

i came up with 2xsuare-2

1) Given that f(x)= 3x-4 and g(x)= x+2

To find f-g:

f(x)-g(x)= 3x-4-(x+2)

= 3x-4-x-2

= 2x-6, so your answer is wrong.

I think maybe you type wrongly for the 2nd problem, it is the same as the first one.

If f(x)=3x-4 and g(x)=x+2: find f-g

just combine

f(x) - g(X) = 3x - 4 - (x +2)

f(x) - g(X) = 3x - 4 - x - 2

combine like terms

f(x) - g(X) = 3x - x - 4 - 2

f(x) - g(X) = 2x - 6

To do f-g you would combine both functions:

(3x-4)-(x+2)

you combine like terms getting:

2x-6